2008
DOI: 10.1143/jjap.47.5248
|View full text |Cite
|
Sign up to set email alerts
|

Cantilever Fabrication by Force-Free Release Transfer

Abstract: Microstructures on a dummy substrate are bonded and transferred to the main substrate in a transfer process. The novel transfer process is developed using a new release layer on the dummy substrate. The release layer consists of a TiO 2 layer and a poly(methyl methacrylate) (PMMA) film. Although the dummy substrate sticks to the main substrate after the bonding, the dummy substrate can be separated from the main substrate without using a pulling force by the UV exposure of the release layer. The force-free rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Adhesion engineering is performed by using a release layer or surface processing to provide a low adhesion of patterns/devices on the donor or pick wafer and/or an adhesion promoting layer/surface processing on the target wafer and/or on the patterns bottom surfaces. Adhesion or fracture strength reduction of the release film can be obtained by H + implantation, by using a porous material, by metal oxidation, by using Self Assembled Monolayers (SAMs), fluorinated polymer films or by UV exposure (1). Likewise, pattern adhesion on the target wafer can be promoted by using other type of SAM, by plasma or UV exposure, by using reactive metals, sealing materials or by thermal way (furnace annealing or laser heating) (5).…”
Section: Donormentioning
confidence: 99%
“…Adhesion engineering is performed by using a release layer or surface processing to provide a low adhesion of patterns/devices on the donor or pick wafer and/or an adhesion promoting layer/surface processing on the target wafer and/or on the patterns bottom surfaces. Adhesion or fracture strength reduction of the release film can be obtained by H + implantation, by using a porous material, by metal oxidation, by using Self Assembled Monolayers (SAMs), fluorinated polymer films or by UV exposure (1). Likewise, pattern adhesion on the target wafer can be promoted by using other type of SAM, by plasma or UV exposure, by using reactive metals, sealing materials or by thermal way (furnace annealing or laser heating) (5).…”
Section: Donormentioning
confidence: 99%
“…[32][33][34] As a similar technique to form a cantilever structure additively, Kawata et al reported the forcefree release transfer based on the photocatalyst effect. 35,36) In their technique, a long UV exposure was necessary to degrade the adhesion between the dummy substrate to transfer a layer. In our novel process, a sufficiently weak adhesion is initially formed at the interface between the PDMS and the printed layer, as explained in the next paragraph, so that rapid fabrication can be achieved.…”
mentioning
confidence: 99%
“…They can be divided in two types: "direct printing" involving one bonding step followed by optional wafer removal (Fig. 1a) 1,2 and a pick and place strategy called "transfer printing", requiring two bonding=debonding steps (Fig. 1b).…”
mentioning
confidence: 99%
“…Adhesion or fracture strength reduction of the release film can be obtained by H þ implantation, 10 by using a porous material, 11 by metal oxidation, 12 by using Self Assembled Monolayers (SAMs), 13 fluorinated polymer films 14 or by UV exposure. 1 Likewise, pattern adhesion on the target wafer can be promoted by using other types of SAM, 15 by plasma 9 or UV exposure, by using reactive metals, sealing materials or by thermal way (furnace annealing or laser heating). 5 The interest of using film transfer technology to enable the fabrication and integration of full films, micro=nano devices or microelectromechanical systems (MEMS) from incompatible technologies has been demonstrated through several works such as, GaAs optoelectronics devices (Laser Diode, Wave Guide and Photo Diode GaAs Optical Link) with standard VLSI technology, 16 CMOS com-patible fabrication of bolometers 17 or monocrystalline silicon mirrors, 6 transfer of silicon onto InP or MgO substrates, 4 InP=InGaAsP dies on silicon-on-insulator waveguide circuits, 18 etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation